BELAJAR MENGURUTKAN ANGKA SECARA VISUAL BERBASIS GAME BERBENTUK GAME PUZZLE: SEBAGAI PENDAHULUAN BELAJAR LOGIKA PEMROGRAMAN - Wahyu Sanjaya; Muhammad Sultan Fauzan; Tedjo Darmanto (STKIP PGRI Situbondo, 2024)
As a learning topic in programming, sorting numbers can be visualized as a puzzle game to increase the engagement of learners in learning the logic of programming through a game. In programming, there are several ways in solving a problem that can be represented by several choices to play a game. In this paper, a sorting game as a puzzle game is chosen in the form of a grid with four rows to four columns. There are four ways to play sorting sixteen arbitrary numbers by exchanging a pair of numbers chosen through the swap as a game feature. The number of steps of each choice can be compared, to which one is the most efficient. So as a game-based learning, sorting numbers as a puzzle game can be used to enhance the engagement of learners to learn introductory programming.